Analisis Nilai Tambah Stik Kulit Kopi Desa Gung Pinto Kabupaten Karo - Priscilla Br Pinem; Fiddini Alham; Muslimah Muslimah (Jurnal Penelitian Agrisamudra, 2022)
This study aims to find out how much it costs to process coffee skins into coffee skin sticks and to find out how much added value and benefit from processing coffee skins into coffee skin sticks. This research was conducted in one of the villages in Naman Teran sub-district, Karo Regency, namely Gung Pinto Village. The samples from this research are two businesses that have business names, namely Stik Sinabung and Usaha Nande Lompoh. The results of this study are the amount of costs incurred by the entrepreneur of processing coffee skin sticks in Gung Pinto Village, which is Rp. 4,690,250.00 in one month of the production process. The added value obtained in each business is 66% in the Sinabung Stick Business and 63% in the Nande Lompoh Business. The profit that can be obtained in one month of production is Rp.3.569.750.00.